PERAN KEPUASAN KERJA SEBAGAI MEDIATOR HUBUNGAN ANTARA PSIKOLOGI CAPITAL DAN DUKUNGAN ORGANISASI TERHADAP PERFORMA KERJA PEGAWAI RS PKU MUHAMMADIYAH KARTASURA - ridwan pamungkas; Bambang Mursito; Supawi Pawenang (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research aims to determine the effect of psychological capital, organizational support, and job satisfaction on employee job performance and the role of job satisfaction as a mediator of the relationship between psychological capital and support for employee job performance at PKU Muhammadiyah Kartasura Hospital. A quantitative research design is used in this research methodology The population of employees who work at PKU Muhammadiyah Kartasura Hospital totals 65 employees. A census with a sample size of 65 respondents served as the sampling method for this investigation. Data collection using a questionnaire. Data analysis techniques using SmartPLS 3.0 software. The results proved that psychological capital, organizational support, and job satisfaction positively and significantly affected employee performance. As well as psychological capital and organizational support have a positive and significant effect on employee job performance at PKU Muhammadiyah Kartasura Hospital. This proves that the combination of psychologically solid capital and good organizational support can create a work environment conducive to employee job satisfaction and, in turn, improve overall work performance.